Satisfaction with the university lecturers’ work in the human resource tertiary education’s management system - I. Yu. Ilina (Вестник университета)
In the conditions of tertiary education’s modernization, the effective management’s importance of the personnel potential’s development of universities increases. One of the significant factors determining the success of management mechanisms in the tertiary education system is the satisfaction with the work of lecturers. The purpose of the study is to assess the level of satisfaction with the work of lecturers, to reveal the significance of its parameters in the management system of the tertiary education’s personnel potential. Based on empirical research data, the article analyzes the most important parameters of work at the university for lecturers and the realization level of the opportunities that work at the university provides. The segmentation author’s version of lecturers according to the level of job satisfaction is proposed, the use of which allows optimizing the process of making managerial decisions based on considering the characteristics of employees’ various segments. The work directions are highlighted on improving the management efficiency of the tertiary school’s personnel potential.